Strategic responses to stakeholder institutional pressures considering complexity in global project - Santos Junior, Heitor Antonio Gomes (2019)
Based on institutional theory, this dissertation aims to analyze the effects of stakeholders??? institutional pressures on temporary organizations???, usually named projects, strategic responses. The inquiry will search for associations between the decisions of project managers to address institutional environment agents??? demands, and the isomorphic processes driven by the need for legitimacy. The role of project complexity in this process is investigated, as a moderator variable, in the interest of identifying the influence of contingency factors. The data will be drawn from project managers and staff in the global project context, since many projects nowadays rely on resources and interactions in a global scale. Furthermore, this arena usually displays aggressive institutional pressures, thus the relevance to scrutinize its influence on project management.